High Stakes Testing and Transformation in the Occupational Identity of Teachers - Omur, Yunus Emre; Bavli, Bunyamin (ISTANBUL UNIV, METHODOLOGY & SOCIOLOGY RESEARCH CENTER, 2020)
In the literature, there is criticism that standardization in education affects the meaning of the teaching profession, the daily practice of the profession, increases the workload of the teacher and acts as a control mechanism on the teacher. The aim of this study is to analyze standard exams and standard programs in terms of the teacher's professional identity and practices, based on the teachers' own experiences. For this purpose, the research was carried out with a phenomenological design, which is one of the qualitative research designs.. The participants of the study were determined by using the purposive sampling technique, which is one of the purposive sampling techniques. Therefore, the study group of the current research consisted of 12 secondary school teachers who had the experience of preparing students for standardized exams, and whose branch was included in those exams. Research data were obtained through in-depth interview and focus group interview techniques, and analyzed with the content analysis method. As a result of the analysis, two themes were created under the title of Teachers Turning into Technicians and Exam Oriented Teaching. These themes are presented and discussed with quotations from the participants' views.
Keywords: Standardized exams; standardized program; teacher identity; ERA; CURRICULUM; EDUCATION; ACCOUNTABILITY; STRESS; Sociology